Assessment of Songwriting Programming Using Basic Psychological Needs Satisfaction Scale: A Study on Inpatient Recovery and Self-Determination - DuTemple, Katie; Wasalinska-Hannah, Regina (Journal of Recovery in Mental Health, 2025)
This study examines the viability of songwriting as a recovery program for patients in a mental health hospital setting. Using the Basic Psychological Needs Satisfaction Scale (BPNSS) as a tool for measuring one’s sense of autonomy, relatedness and competence, first-time participants were asked to complete the scale before and directly following a one-hour songwriting session, with open-text questions included in the post-intervention scale.Forty-nine participants from two different inpatient units - Crisis and Critical Care (CCC) and Medical Withdrawal Services (MWS) - volunteered to take part in the study. Results indicated that only participants from CCC saw a statistically significant increase in competence mean scores, with open-text responses from both units supporting this finding. Common sentiments from open-text responses included growth in confidence and self-belief, elevation in mood, and expression of emotions through creative practice. Developing a sense of competence can be important when entering into recovery and can lead to an increase in confidence. While the initial findings from this pilot study are promising, further research is needed to determine the efficacy of songwriting as a mental health support.